IMPROVING FUTURE ENGLISH TEACHERS’ CREATIVITY THROUGH TASKS - Pulatova Durdona Ravshanovna (Bright Mind Publishing, 2025)
Creativity is a crucial skill for future English teachers, enabling them to develop engaging, dynamic, and effective language learning environments. This study explores how task-based learning (TBL) can enhance creativity among future educators by requiring them to design and implement innovative teaching techniques. The study involved 100 part-time students from ISFT, who were tasked with creating unique methodologies for teaching language skills, applying them in real classroom settings, and reflecting on their experiences. The findings indicate that task-based activities significantly improve teachers’ ability to develop innovative strategies, enhance student engagement, and foster self-reflection, making them more adaptive educators.
Keywords: Creativity, task-based learning, English language teaching, innovation, future teachers, methodology.